Knowledge Management Technology: Current Perception By Small And Medium Enterprise (SME) - Ab Aziz, Azira (2008)
This paper reports a study of whether such benefits through the integration of KM technologies can be substantiated for SMEs. Defining appropriate KM technologies is the central objective of the study. The factors influencing the perception of technical readiness for KM implementation in SMEs and the general perceived awareness of KM technologies including reluctance among SMEs are also reported